Effects and Mechanisms of Symbiotic Microbial Combination Agents to Control Tomato Fusarium Crown and Root Rot Disease - Cai, Xinyue; Zhao, Honghai; Liang, Chen; Li, Min; Liu, Runjin (Frontiers in Microbiology, 2021)
This study evaluated the effects and underlying mechanisms of different combinations of plant symbiotic microbes, comprising arbuscular mycorrhizal fungi (AMF), plant growth-promoting rhizobacteria (PGPR), and Trichoderma spp., on tomato Fusarium crown and root rot (TFCRR) resistance. A total of 54 treatments were applied in a greenhouse pot experiment to tomato (Solanum lycopersicum) seedlings inoculated with or without Funneliformis mosseae (Fm), Rhizophagus intraradices (Ri), Trichoderma virens l40012 (Tv), Trichoderma harzianum l40015 (Th), Bacillus subtilis PS1-3 (Bs), Pseudomonas fluorescens PS2-6 (Pf), and Fusarium oxysporum f. sp. radicis-lycopersici (Fo). The symbioses on the tomato root system were well developed, and the composite symbiont generated by AMF + Trichoderma spp. was observed for the first time. Compared with other treatments, Ri + Bs + Tv and Fm + Pf + Tv stimulated the greatest improvements in tomato growth and yield. The combination Ri + Pf + Th + Fo resulted in the strongest biocontrol effects on TFCRR, followed by the treatments Th + Pf + Fo and Ri + Th + Fo. Compared with the Fo treatment, most inoculation treatments improved photosynthetic performance and significantly increased defense enzyme activity in tomato plants, of which the treatment Ri + Pf + Th + Fo showed the highest enzyme activity. Metabolome analysis detected changes in a total of 1,266 metabolites. The number of up-regulated metabolites in tomato plants inoculated with Ri + Pf + Th and Ri + Pf + Th + Fo exceeded that of the Fo treatment, whereas the number of down-regulated metabolites showed the opposite trend. It is concluded that AMF + Trichoderma + PGPR is the most effective combination to promote resistance to TFCRR in tomato. The up-regulation and down-regulation of metabolites regulated by symbiotic microbial genes may be an important mechanism by which root symbiotic microorganisms promote plant growth, increase yield, and improve disease resistance.